(untitled) (Vietnam Journal of Community Medicine, 2021)
Objectives: The study demonstrated the clinical symtoms of patients with multidrug-resistant tuberculosis (MDR-TB) and addressed the safety of standardised, shorter MDR-TB regimens Methods: The cohort study was conducted with 124 patients with MDR-TB. All patients were treated by standardised, shorter MDR-TB regimens in Hanoi Lung Hospital from April 2016 to December 2018. Results: Sputum smear results were 47,6% AFB (-), 5.6% AFB(3+), 7.3% AFB (2+), 35.5% AFB (1+) and 4.0% 1-9 AFB/100VT. Radiological signs were 70.2% fbrosis, 67,7% node, 56,6% infliltrate and 16.9% cavity. 62.9% patients had lesions in both lungs. Safety ratio was 58.9%. Adverse events were 10.5% dyspepsia, 8.9% vomiting, 8.9% dizzy, 8.1% anorexia, 4.8% athritis and 4.3% hearing loss. Conclusion: The standardised, shorter MDR-TB regimens was safety with less adverse events. All of the side eﬀect symptoms had recovered after fnishing treatment.